Interactions of Enolizable Barbiturate Dyes. Issue 16 (4th March 2016) - Schade, Alexander; Schreiter, Katja; Rüffer, Tobias; Lang, Heinrich; Spange, Stefan
Abstract: The specific barbituric acid dyes 1‐ n ‐butyl‐5‐(2, 4‐dinitro‐phenyl) barbituric acid and 1‐ n ‐butyl‐5‐{4‐[(1, 3‐dioxo‐1 H ‐inden‐(3  H )‐ylidene)methyl]phenyl}barbituric acid were used to study complex formation with nucleobase derivatives and related model compounds. The enol form of both compounds shows a strong bathochromic shift of the UV/Vis absorption band compared to the rarely coloured keto form. The keto–enol equilibria of the five studied dyes are strongly dependent on the properties of the environment as shown by solvatochromic studies in ionic liquids and a set of organic solvents. Enol form development of the barbituric acid dyes is also associated with alteration of the hydrogen bonding pattern from the ADA to the DDA type (A=hydrogen bond acceptor site, D=donor site). Receptor‐induced altering of ADA towards DDA hydrogen bonding patterns of the chromophores are utilised to study supramolecular complex formation. As complementary receptors 9‐ethyladenine, 1‐ n ‐butylcytosine, 1‐ n ‐butylthymine, 9‐ethylguanidine and 2, 6‐diacetamidopiridine were used. The UV/Vis spectroscopic response of acid–base reaction compared to supramolecular complex formation is evaluated by 1 H NMR titration experiments and X‐ray crystal structure analyses. An increased acidity of the barbituric acid derivative promotes genuine salt formation. In contrast, supramolecular complex formation is preferred for the weaker acidic barbituric acid. Abstract : Optically visible recognition : Chromophoric barbituric acid derivatives containing an electron‐withdrawing group can switch between enol and keto form depending on the environment. Competition between genuine salt formation or supramolecular interactions was found for interaction of the barbiturate dyes with nucleobase derivatives and 2, 6‐diacetamidopyridine. Thus, optical response can be used to distinguish between nucleobase derivatives.